Bentuk Kucing Sebagai Pola Hias Bingkai Cermin (Qualia: Jurnal Ilmiah Edukasi Seni Rupa dan Budaya Visual, 2021)
In everyday life, mirroring is one of the human needs in improving the appearance of oneself, especially in the facial area. Indonesia is a country that has various types of wood as a source of natural wealth, one of which is mahogany, so it is not surprising that wood is the main material for making mirror frames on the market. The development of popular culture (make-up activities) which has become a trend in the behavior of adolescents in Indonesia encourages the author to create a functional and aesthetic work as a decorative complementary object in the form of a hagging mirror, which is specifically for young girls aged 20-27 years. when doing make up. The shape of the body silhouette of a cat type Felis Silvetris Catus or a village cat was chosen as a visual form of a mirror frame pattern, because in Islam, cats have the privilege of being the Prophet Muhammad's favorite animal